Pelatihan Pembuatan Media Pembelajaran Interaktif Bentuk Presenter-View-Recorder dan Mentimeter - Sari , Rafika; herlawati, herlawati; Khasanah, Fata Nidaul; Atika, Prima Dina (Jurnal Pengabdian kepada Masyarakat UBJ, 2021)
During the Covid-19 pandemic, most educators used social media to deliver learning material files without verbal explanation, unlike face-to-face learning in class. Through these limited facilities, it has an effect between teachers and students experiencing interaction problems which can be used as a benchmark for the absorption of the material provided by the teacher and understanding of the material for students. Based on this problem, we took the initiative to make community service activities by providing training on the use of the Powerpoint Presenter-View-Recorder and Interactive Mentimeter applications as interaction media in online learning, which are still rarely used by teachers, especially at SMPN 264 Jakarta. The implementation of this training program aims to provide breakthroughs in teaching. Students are expected not to be bored while participating in learning activities. The innovation used is by optimizing the Powerpoint application in the form of Presenter-View-Recorder as well as using the Interactive Mentimeter application and directly uploading learning videos that have been made to the Google Classroom application and Youtube social media.